Energy-saving texnologies and alternative energy sources - Abdunabiyeva Noila Yusufjon qizi (Proceedings of The ICECRS, 2020)
The energy problem is one of the most pressing issues in the world is on the agenda of scientists working in the field of energy. XXI century with the development of science, rising technology creating the opportunity for a person to live normally, providing him with enough energy, food is one of the key issues. Everyone knows digging the energy reserves of its resources are declining. But the need for it increased, and now the world's population has reached seven billion. There are the following types of energy sources that used by humanity: oil, coal, gas, atom, biomass, water, solar, wind, geothermal energy. This energy sources can be divided into two types, respectively. Biomass, water, sun, wind, geothermal energy - renewable; oil, coal, gas, nuclear energy - non-renewable. The energy from these resources is electricity, utilities such as energy consumed for services (heating of buildings, hot water supply) occurs in views.